L-alanil-glutamina em modelo experimental de lesão aguda pulmonar induzida por trauma muscular esquelético - Sombra, Márcia Andréa Silva Carvalho (2009)
In this study we aimed to validate a model of acute lung injury (ALI) induced by surgical muscle trauma, which attempts to reproduce the conditions of a skeletal muscle trauma that occurs in humans and, therefore, to provide a better understanding of this disease and its treatments’ alternatives. In the first step we evaluated the effect of the experimental model. Thirty-six male Wistar rats with average weight of 250g, were divided into 6 groups. In the first step we evaluated the effect of the experimental model. Saline Group (n = 6): animals received 2 ml of saline (i.v) at the same times of the Saline and trauma group; Saline and Trauma Group (n = 6): animals received saline 30 minutes before the induction of muscle trauma and again at 6 and 12 hours after the trauma; Dexamethasone Group (n = 6): animals received 2 doses of dexamethasone 2 mg / kg (i.p) at the same times of Dexamethasone and Trauma Group; Dexamethasone and Trauma Group (n = 6): animals received 2 doses, 2 hours before the occurrence of trauma and 10 hours after the trauma - this group was used as positive control. Surgical procedures were performed under anesthesia of tribromethanol 2.5% (1 ml/100g body weight). The induced trauma surgery was performed in the thigh of the animal and every muscle was detached from the knee to the hip joint. After 24 h of injury, the lungs were retreated to evaluate myeloperoxidase (MPO), glutathione (GSH), neutrophil infiltration, congestion, edema, necrosis and hemorrhage. In plasma only GSH was measured. It was observed that the muscle trauma was shown to induce ALI by promoting a significant reduction in GSH (8.53 ± 1.22 versus 18.87 ± 7.35 p <0.01) and a significant increasing activity of MPO (23.96 ± 4.86 versus 24.50 ± 7.45 p <0.001), neutrophil infiltration (71.00 versus 19.64 ± 28.50 ± 7.63 p <0.001), degree of congestion, edema, necrosis and hemorrhage (p <0.01), when compared with Saline Group without trauma. In Dexamethasone and Trauma Group, when compared to Saline and Trauma Group, Dexamethasone, by being an inhibitor of inflammatory gene, was able to modulate the inflammatory response in almost all parameters. Subsequently we evaluated the effect of L-alanyl-glutamine (L-Ala-Gln) on acute lung injury induced by muscle trauma surgery. 24 h after trauma it was made a comparison between the group treated with L-Ala-Gln and trauma (n = 6) and the saline and trauma group, and it was found that L-Ala-Gln promoted a statistically significant reduction in neutrophil infiltration ( 19.64 ± 71.00 versus 28.50 ± 7.63 p <0.001), in MPO activity (23.96 ± 4.86 versus 12.90 ± 2.01, p <0.001) and a significant increase in concentration of GSH (36.79 ± 7.31 versus 8.53 ± 1.22 p <0.001) in the lung. In histopathological evaluation it was also observed a significant decrease (p <0.01) in the degree of edema, hemorrhage and necrosis in lung tissue of the evaluated groups above. The possible mechanism to justify the observed effects could be that glutamine enhanced glutathione levels, the energy substrate for immune cells, and, additionally, increased the expression of heat shock proteins (HSP) and, as such, prevented the infiltration of neutrophils in tissues. These results suggest that the Ala-Gln treatment has the potential to reduce the inflammatory reaction that was installed in lungs after skeletal muscle trauma.